2013
DOI: 10.1111/ajd.12033
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular metastatic melanoma: A difficult diagnosis

Abstract: Melanoma is a common cancer with the potential for widespread metastasis; however intravascular metastasis is extremely rare. We report an unusual case of a patient with metastatic melanoma in whom (18) F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) demonstrated an intravascular melanoma metastasis in the superior vena cava (SVC), successfully treated with external beam radiotherapy. To our knowledge, this is the first reported case where FDG PET-CT was used to make this dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Although melanoma is an aggressive form of skin cancer with the propensity for lymphatic spread to lymph nodes and haematogenous spread to distant organs, tumour thrombi are rarely reported. Sites of reported venous involvement by metastatic melanoma include the superior vena cava, the inferior vena cava, and the pulmonary, portal, renal, femoral and great saphenous veins 2‐11 . Similarly to our case, most cases presented a number of years after the initial primary cutaneous melanoma.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although melanoma is an aggressive form of skin cancer with the propensity for lymphatic spread to lymph nodes and haematogenous spread to distant organs, tumour thrombi are rarely reported. Sites of reported venous involvement by metastatic melanoma include the superior vena cava, the inferior vena cava, and the pulmonary, portal, renal, femoral and great saphenous veins 2‐11 . Similarly to our case, most cases presented a number of years after the initial primary cutaneous melanoma.…”
Section: Discussionsupporting
confidence: 75%
“…Sites of reported venous involvement by metastatic melanoma include the superior vena cava, the inferior vena cava, and the pulmonary, portal, renal, femoral and great saphenous veins. [2][3][4][5][6][7][8][9][10][11] Similarly to our case, most cases presented a number of years after the initial primary cutaneous melanoma. One case presented as an extension into the inferior vena cava from a primary adrenal melanoma.…”
Section: Discussionsupporting
confidence: 68%
“…Ghattas et al reported a case of melanoma of the left axilla with intravascular metastasis to the lower SVC which was also hypermetabolic on PET/CT, but with no central catheter present [4]. Bland non-catheter-related thrombus often has a lower SUV max compared to tumor thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intraluminal metastasis to the SVC from DASCs has not been reported previously. To date, only a limited number of cases of malignant neoplasms of the skin ( 12 , 13 ), prostate ( 14 ), lung ( 15 ), thyroid ( 16 ), thymus ( 17 ) and colon ( 18 ) with intraluminal metastases to the SVC have been reported ( Table I ). We hypothesize that metastases to the large vessels are extremely rare due to the high volume and speed of blood flow, and the thick sub-endothelial layer, which prevent invasion by tumor cells.…”
Section: Discussionmentioning
confidence: 99%